Current Understanding of the Role of Frailty in Cardiovascular Disease - Uchikado, Yoshihiro; Ikeda, Yoshiyuki; Ohishi, Mitsuru (Circulation journal : official journal of the Japanese Circulation Society, 2020)
The elderly population is increasing because of increasing life expectancy, and the prevalence of frailty increases with age. Frailty commonly coexists with cardiovascular diseases (CVDs), such as coronary artery disease (CAD), heart failure (HF), aortic stenosis (AS), and atrial fibrillation (AF). Frail patients who undergo revascularization for CAD have higher complication rates; those with HF have a high prevalence of poor outcomes, and those with AF are vulnerable to increased stroke incidence. Moreover, frailty and asymptomatic severe AS were independent factors for mortality. The presence of frailty can lead to poor clinical outcomes, and frailty has been identified as a risk factor for mortality. Thus, the identification of frail patients who are at higher risks of disability and adverse clinical outcomes is important. In this review, the relationship between frailty and CVD is appraised and optimal treatments for frail patients are discussed.